Prevalence of Cow Milk Protein Intolerance in Infants With Failure to Thrive - Saadat, Rabeea; Ijaz, Nayab; Wamiq, Saba; Javeed, Asif; Saleem, Seemab; Chaudhary, Momal (Biological and Clinical Sciences Research Journal, 2025)
Failure to thrive (FTT) in infants is a common clinical concern, with multiple etiologies, including food allergies. Cow milk protein intolerance (CMPI) is one of the most prevalent food allergies in infants and can contribute to FTT. The prevalence of CMPI in infants with FTT in Pakistan remains underexplored, warranting this investigation. Objective: To determine the prevalence of cow milk protein intolerance (CMPI) in infants with failure to thrive in Pakistan's hospital setting. Methods: A descriptive cross-sectional study was conducted from February 2023 to July 2024 at Ibn-e-Siena Hospital, Multan. A total of 149 infants with FTT, defined as weight and length below the 5th percentile for age, were selected using stratified random sampling. Infants exclusively fed cow milk were placed on an elimination diet to identify CMPI. The presence of CMPI was confirmed if symptoms resolved following the elimination of cow milk. Results: Of the 149 infants with FTT, 70 (46.2%) were exclusively fed cow milk and showed signs of improvement after cow milk elimination, indicating a CMPI prevalence. Thirty-two infants (21.4%) were fed both cow milk and other milks, while 40 infants (26.8%) had co-morbidities such as congenital heart disease and cystic fibrosis, which contributed to their failure to thrive. Seven infants (4.6%) had an undetermined cause of FTT. Conclusion: Cow milk protein intolerance is a significant contributor to failure to thrive in infants in Pakistan, with nearly half of the infants with FTT exhibiting CMPI. Awareness of CMPI as a potential cause of failure to thrive should be increased among healthcare providers. Early diagnosis and dietary modifications can improve growth and development outcomes in affected infants. Larger studies are needed to confirm these findings and guide policy changes for managing the stability of infant food allergies.